A favourable solubility of isoniazid, an antitubercular antibiotic drug, in alternative solvents - Forte, Andreia (2013)
The sufficient solubility of isoniazid in alternative solvents obtained in this work can open new perspectives in pharmaceutical processing. Solid–liquid equilibrium (SLE) measurements have been made using a dynamic (synthetic) method. The melting point and the enthalpy of fusion of isoniazid were acquired using differential scanning calorimetry (DSC). The solubility of isoniazid in bis(trifluoromethylsulfonyl)amide ionic liquids was found to be significantly lower than in the studied trifluoromethanesulfonate ionic liquid. The best solvent amongst studied for this common antibiotic against tuberculosis was discovered. The solid–liquid phase equilibria were described using the six different correlation equations which revealed relatively good description with the acceptable standard deviation temperature range.